2020
DOI: 10.3390/electronics9081211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Electromagnetic Performance of Active Phased Array Antenna

Abstract: Active phased array antennas (APAAs) can suffer from the effects of harsh thermal environments, which are caused by the large quantity of power generated by densely packed T/R modules and external thermal impacts. The situation may be worse in the case of limited room and severe thermal loads, due to heat radiation and a low temperature sink. The temperature field of the antenna can be changed. Since large numbers of temperature-sensitive electronic components exist in T/R modules, excitation current output ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This study calculated the impinging jet flow and convective heat transfer based on the governing equations, such as the continuity equation, momentum equation, and energy equation which are presented below Eq [ 2 ] - [ 4 ]; …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study calculated the impinging jet flow and convective heat transfer based on the governing equations, such as the continuity equation, momentum equation, and energy equation which are presented below Eq [ 2 ] - [ 4 ]; …”
Section: Methodsmentioning
confidence: 99%
“…However, the temperature and cooling problem within the X-band radar is becoming an issue due to the increasing number of high power T/R modules and semiconductor integration to ensure the operations of the radar during military action. The radar output power varies greatly depending on the T/R module temperature, and when the temperature is 80 °C or higher, the active electronically scanned array (AESA) radar output power drops sharply [ 4 ]. To prevent temperature rise in the T/R module, its devices generating a large output power are made of materials with high thermal conductivity for heat dissipation or cooling channels are installed inside/outside the T/R module [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emission direction of the electromagnetic wave depends on the phase differences of all T/R modules [ 1 ]. The power of each T/R module is in the KW level [ 2 ], so, the T/R module generates a lot of heat. Therefore, the panel of the PAA has a sizeable thermal deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [ 5 ] found that thermal deformation causes the gain of the main lobe to decay. Wang et al [ 2 ] and Wang et al [ 6 ] established a coupled structural–electromagnetic–thermal model by the finite element method (FEM), which provides some theoretical guidances for the structure design of the phased array antenna. H. Ren [ 7 ], Han et al [ 8 ], and Zhang et al [ 9 ] optimized and simulated the heat dissipation system of a phased array radar.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the interconnection configuration will be forced to deform under the influence of the envi-ronmental stress load, which will further affect the electrical signal transmission. The superposition of the two parts can cause the failure of the electrical transmission function of the module in some extreme cases [4,5]. On the other hand, mechanical reliability problems in the process of design, manufacture and operation of the microwave circuit interconnection can directly cause circuit function failure [6].…”
Section: Introductionmentioning
confidence: 99%